Exclusive Breastfeeding History with The Incidence of Stunting in Children Aged 6-24 Months - Sumarah Sumarah; Munica Rita Hernayanti (Jurnal Bidan Cerdas, 2025)
Background: Stunting is nutritional health issues in Indonesia affecting children under 5 years. Numerous variables, including exclusive breastfeeding, can contribute to stunting. This study aims to find out the influence of history of exclusive breastfeeding to stunting in children between the ages of 6 and 24 months in the Turi Health Center working area. Methods: This study used a case-control study design and an observational-analytic sampling with a simple random sampling method. All children aged 6-24 months in Turi Health Center's toddler registration who met the inclusion and exclusion criteria were listed as study subjects. There were 100 subjects with 50 subjects being cases and 50 subjects being controls. Data analysis used univariable, bivariable using Chi-square, and multivariable using logistic regression. Results: The characteristics of respondents with male and female gender had the same proportion (50%), while the children age were mostly 13-24 months old (62%). Most of respondents had a history of exclusive breastfeeding (80%) dan had never experiencing infectious diseases (58%). The findings demonstrated a significant correlation between exclusive breastfeeding history and stunting among children aged 6-24 months with a p-value of 0.012 OR 3.857 (95% CI:1.278-11.638). Conclussion: Exclusive breastfeeding is one of the keys to provide sufficient nutrients among children under five. Exclusive breastfeeding continues to be promoted to decrease the prevalence of stunting in children aged 6-24 months.or exploring other variables that influence labor progress.